ANALISIS FAKTOR YANG MEMPENGARUHI PERMINTAAN CABAI MERAH (Capsicum annum L) DI KABUPATEN LABUHANBATU - Khairul Rizal; Junita Lubis; Yusmaidar Sepriani (UNIVERSITAS LABUHANBATU, 2021)
Red chili (Capsicum annum L) is a type of horticultural vegetable that is widely cultivated in Indonesia. Red chilies have a high price and this plant is very beneficial for health. One of them is controlling cancer. This study aims to determine the analysis of the factors that influence the demand for red chili in Labuhanbatu Regency. The analytical method used in this research is multiple linear regression analysis, classical assumption test and statistical test. The results of the study based on the t test that the price has a positive effect on the demand for chili peppers in Labuhanbatu Regency, the tcount value is 2.417 with a significance level of 0.002 and the population has a significant effect on the demand for chili in Labuhanbatu Regency, the tcount value is 3.298 and a significance level is 0.001. Keywords : beneficial, horticultural, red chili, regression analysis